2006
DOI: 10.1016/j.bbmt.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Purging by Ex Vivo Expansion of Hemopoietic Stem Cells from Breast Cancer Patients Combined with Targeting ErbB Receptors

Abstract: Tumor cell contamination might induce relapse after autologous transplantation in breast cancer patients. We used an ex vivo purging strategy to decrease the number of contaminating breast tumor cells in leukaphereses without altering the engraftment potential of the hemopoietic progenitor cells. This method is based on immunoselection of CD34+ cells derived from mobilized peripheral blood of patients with metastatic breast cancer and expansion in the presence of flt3 ligand, stem cell factor, interleukin 6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, in the case of a known tumor antigen, it is also possible to presensitize a normal donor, as described by Kwak et al and others (44, 45). In addition, tumor cell purging of ex vivo expanded hematopoietic stem cells has been successfully implemented in autologous transplant for both liquid and solid tumors (46, 47). …”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of a known tumor antigen, it is also possible to presensitize a normal donor, as described by Kwak et al and others (44, 45). In addition, tumor cell purging of ex vivo expanded hematopoietic stem cells has been successfully implemented in autologous transplant for both liquid and solid tumors (46, 47). …”
Section: Discussionmentioning
confidence: 99%
“…Only 6 out of 17 studies reported the ER/PR/HER2 status of the breast tumor in patients [6,9,20,23,28,36]. Six studies utilized the CO regimen [20,25,26,27,28,36], 4 studies used the C+C regimen [8,10,24,33], and 7 studies compared both CO and C+C regimens [6,9,22,23,29,35,37]. Eleven studies used immunocytochemistry of cytokeratin [5,8,10,20,22,25,26,27,35,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 1995 and 2006 and are summarized in table 1. Most of the studies included stage IV breast cancer patients [5,6,9,10,20,22,23,24,25,26,27,28,29,30,31,32,33,34]; however, some studies also included high-risk stage II and III patients [5,22,25,26,27,29,32,34,35,36,37]. The percentage of patients evaluated with stage II/III and stage IV disease was not significantly different in the CO versus C+C groups (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation